Resin-dentin bond stability of etch-and-rinse adhesive systems with different concentrations of MMP inhibitor GM1489 - Miranda, Maria Elisa da Silva Nunes Gomes; Silva, Eduardo Moreira da; Oliveira, Mariana Flôres de; Simmer, Fabiana Souza; Santos, Glauco Botelho dos; Amaral, Cristiane Mariote (Journal of Applied Oral Science, 2021)
Enzymatic degradation of the hybrid layer can be accelerated by the activation of dentin metalloproteinases (MMP) during the bonding procedure. MMP inhibitors may be used to contain this process. Objective: To evaluate the degree of conversion (DC%), dentin bond strength (µTBS) (immediate and after 1 year of storage in water), and nanoleakage of an experimental (EXP) and a commercial (SB) adhesive system, containing different concentrations of the MMP inhibitor GM1489: 0, 1 µM, 5 µM and 10 µM. Methodology: DC% was evaluated by FT-IR spectroscopy. Dentin bond strength was evaluated by µTBS test. Half of beams were submitted to the µTBS test after 24 h and the other half, after storage for 1 year. From each tooth and storage time, 2 beams were reserved for nanoleakage testing. Data were analyzed using ANOVA and Tukey’s test to compare means (α=0.05). Results: All adhesive systems maintained the µTBS after 1 year of storage. Groups with higher concentrations of inhibitor (5 µM and 10 µM) showed higher µTBS values than groups without inhibitor or with 1 µM. The nanoleakage values of all groups showed no increase after 1 year of storage and values were similar for SB and EXP groups, in both storage periods. The inhibitor did not affect the DC% of the EXP groups, but the SB5 and SB10 groups showed higher DC% values than those of SB0 and SB1. Conclusions: The incorporation of GM1489 in the adhesive systems had no detrimental effect on DC%. The concentrations of 5 µM GM1489 for SB and 5 µM or 10 µM for EXP provided higher μTBS than groups without GM1489, in the evaluation after 1 year of storage; whereas the concentration of inhibitor did not affect adhesive systems nanoleakage.